PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Food and Baverage Yang Terdaftar Di BEI Periode 2013-2016) - Anita Laelatul Khomsatun; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRAK                Some parties consider dividends have no effect on the value of the company known as the irrelevance of devidend proportion, this party sees that dividends have relevance to the value of the company called the relevance of devidend proportion. The purpose of this study was to determine the influence of these factors on the value of the company. To test the hypothesis, secondary data was used with purposive sampling method.                Data analysis techniques use path in analysis with profitability as an exogenous variable and dividend policy as an intervening variable and firm value as an endogenous variable. After the data was analyzed, it was found that profitability and dividend policy had a significant effect on firm value, while the effect of profitability on dividend policy was not significant.Keywords: profitability, company value and dividend policy.